Respuesta agronómica del cultivo de rábano (Raphanus sativus) a la aplicación de abonos orgánicos - Carrera Bastidas, Jonatan Vicente (2015)
In the study conducted at the Experimental Center "La Playita" located UTC geographic WGS 84: Latitude S0 ° 56 '27 "Longitude W 79 ° 13' 25"; taken as study objectives, determine the organic fertilizers preparation from animal waste and plant residues as well as measuring the response of organic fertilizers in the cultivation of radish, evaluate some indicators of growth in radish plants and evaluate the analysis economic development of the most promising treatments in radish plants. Using a completely randomized design (CRD) with two treatments and a control with seven repetitions.....